ANALISIS FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA MELANJUTKAN STUDI S2 DI UNIVERSITAS NEGERI PADANG - Nadia Guspiani Putri; Oknaryana (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Abstract.This research aims to find out what factors influence students' interest in continuing their Masters studies at Padang State University. This type of research is quantitative research using exploratory factor analysis techniques. The population in this study were all undergraduate students at the Faculty of Economics at Padang State University. The sample size in this study was taken using the Slovin formula with a sample size of 81 respondents. Then, the sampling technique in this research is Proportional Random Sampling. The data collection tool in this research is a questionnaire, which is prepared in the form of a Likert Scale with five alternative answers whose validity and reliability have been tested. Data were analyzed using the average formula (mean). The results of the research show that based on 20 factor variables tested using factor analysis, it is known that there are 10 factor variables which are factors that influence students' interest in continuing their Masters studies at Padang State University. The 10 factors are 1) quality and career motivation, 2) family environmental factors, 3) parents' socio-economic conditions, 4) future expectations factors, 5) peer environment factors, 6) social motivation factors, 7) education cost factors, 8) economic motivation factors, 9) parental encouragement factors, 10) learning achievement factors.